2005
DOI: 10.2166/wst.2005.0110
|View full text |Cite
|
Sign up to set email alerts
|

Stormwater quality models: sensitivity to calibration data

Abstract: Stormwater quality modelling is a useful tool in sewer systems management. Available models range from simple to detailed complex ones. The models need local data to be calibrated. In practice, calibration data are rather lacking. Only few measured events are commonly used. In this paper, the effect of the number and the variability of calibration data on models of various levels of complexity are investigated. The study is carried out on "Le Marais" catchment for suspended solids where 40 reliable measured ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
10
0
2
Order By: Relevance
“…Much work has been done on calibration (e.g. Kanso et al 2003;Madsen 2003;Mourad et al 2005;Kavetski et al 2006;Thyer et al 2006;Frost et al 2007) and uncertainty of urban storm water models (e.g. Lei & Schilling 1996;Bertrand-Krajewski et al 2003;Kanso et al 2005;Korving & Clemens 2005;Kuczera et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Much work has been done on calibration (e.g. Kanso et al 2003;Madsen 2003;Mourad et al 2005;Kavetski et al 2006;Thyer et al 2006;Frost et al 2007) and uncertainty of urban storm water models (e.g. Lei & Schilling 1996;Bertrand-Krajewski et al 2003;Kanso et al 2005;Korving & Clemens 2005;Kuczera et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Even the simplest regression models have an additional calibration coefficient to SMC estimates, implying they will not perform well at sites with limited sampling, potentially overfitting on smaller datasets. This is supported by Mourad et al (2005aMourad et al ( , 2005bMourad et al ( , 2005c and Obropta and Kardos (2007) who suggested that SMCs required fewer data than regression or build-up washoff models. Furthermore, the study by May and Sivakumar (2013) found that the flow-weighted mean began performing less accurately on smaller datasets, potentially due to outlying storm event(s), which dominated the calibration of SMC.…”
Section: Authors' Replymentioning
confidence: 69%
“…Multi-purpose advice for optimal sensor placement in any kind of urban water system network are presented in the PREPARED project [17], where also detailed locations for pollutant measures are considered, e.g., the position within the cross-section in dependence to the flow distribution. The majority of these studies however concentrate on conceptual drainage models [1], pluvial flood models [16] or pollutant models [18][19][20], respectively. Focus is laid therein on the quantification of mass fluxes, either to the receiving water bodies via combined sewer overflows or to the wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%